PELATIHAN DAN PENDAMPINGAN PERHITUNGAN RAB DI SEKOLAH ALAM AR RIDHO SEMARANG - Faizal Mahmud; Kukuh Wisnuaji Widiatmoko; Son Haji (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2023)
In building infrastructure or building construction, cost calculations are required which are prepared in the form of a Cost Budget Plan (RAB) according to the standards set by the government. RAB provides an overview of the costs of work required to build infrastructure or building construction. Apart from that, from the RAB calculation you can also find out the need for materials or building materials, the number of workers needed and the duration of implementation time to complete the work. The aim of this Community Service activity is to provide insight and knowledge to the management of the Ar Ridho Nature School Semarang about how to calculate the Budget Plan (RAB) in infrastructure development. The implementation method begins with interviews regarding understanding of the Cost Budget Plan (RAB), socialization of the benefits of calculating the Cost Budget Plan (RAB), training and practice in calculating the Cost Budget Plan (RAB), monitoring and evaluation. It is hoped that from this Community Service activity, managers will gain knowledge on how to calculate RAB by better understanding how to calculate work volumes, determine material prices / work unit prices, so that during construction implementation there will be no cost overruns